Response of Growth and Agronomic Characters of Some Triticale and Barley Genotypes for Different Seeding Rates - Mohammad, M. T.; Mohammed, C. H. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Two experiments were carried out during winter season of 2010-2011 at two different locations Halabja and Qlyasan research station in order to study the response of some triticale (Roaeda, Eronga-95 and Clossbied) and barley (IPA 99, Bip 999 and NS 313) genotypes under four different seeding rates (80, 120, 160, 200 kg/ha), and their interactions on some growth and agronomic characters. Using Split Plot Design in which main plots in RCBD with three replications. The results showed significant differences among genotypes for all agronomic characters at both locations and their average with the exception of flag leaf area and flag leaf dry weight during Qlyasan location. The statistical analysis revealed non significant effects of seeding rates on growth and agronomic characters at both locations and their average with the exception of number of days from seeding to physiological maturity, which was highly significant at both locations with their average. There were no significant differences due to the effect of interaction between genotypes and seed rates on growth and agronomic characters at both locations and their average.
Keywords: Genotypes barley triticale hybrid breeding seeding rates agronomic